PERANCANGAN SISTEM INFORMASI ADMINISTRASI PENJUALAN JASA PADA PERCETAKKAN SEDULUR DENGAN ANALISIS PENERAPAN METODE USABILITY - Sri Tita Faulina; Novi Lestari (Jurnal Informatika dan Komputer (JIK), 2019)
In this study several methods used in collecting the required data are Observation Method, Reference Method and Interview Method. The results of this study are an Information Systems application that can manage Sales Service Administration data, providing convenience in processing data, searching, Inventory and Sales Data Services, which are Service Information Administration Services Services at Sedulur Printing. consists of 6 menus, such as Files, Input Data, Transactions, Report Search, Admin and Logout And with analysis Based on the thought of using the Usability method which is expected to produce applications or systems that are effective, efficient, safe in its use, easy to learn / understand, remember, and have good utility